“The Night Watch is Going Through Amsterdam”: Rembrandt’s Painting in the Lyrical Plot - Малкина, Виктория (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
This paper is devoted to the problem of visual representation in a lyric text. The main problem that is solved in the paper is the following: how is Rembrandt Van Rijn’s painitng titled Performance of the rifle company of Captain Frans Banning Kok and Lieutenant Willem Van Ruytenburg (1642) – better known in the history of culture as The Night Watch – presented in the lyrical plot of poems by various authors. The material of the paper consists of the works in which the painting by Rembrandt is in the centre of the lyrical plot, but not merely mentioned. These include: Alexander Kushner’s poem “The Night Watch” (1966), the song “The Night Watch” by King Crimson (1974), “Ayreon’s” song “The Shooting Company of Captain Frans B. Cocq” (2000), and Alexander Gorodnitsky’s poem “The Night Watch: Painting by Rembrandt van Rijn” (2019). To achieve the goal, several tasks are solved in the paper. First, the conceptual apparatus is determined, which includes categories such as ekphrasis, lyric plot, and the visual in literature. Second, the selected texts are analysed from the point of view of the use of Rembrandt’s paintings in them. And, finally, the works are compared with each other and a conclusion is made about what features the The Night Watch paining acquires, falling into the context of a lyric poem.